2002
DOI: 10.17660/actahortic.2002.570.45
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Origin of Lilium Longiflorum and L. Formosanum Ii -Intra- And Interspecific Variation in Stem Leaf Morphology, Flowering Rate and Individual Net Production During the First Year Seedling Growth

Abstract: Lilium longiflorum and L. formosanum are closely related species endemic to subtropical islands in the Ryukyu Archipelago and Taiwan. Stem leaf morphology, flowering rate within population and individual net production during the first year seedling growth were determined to clarify whether they can differentiate these two species, and reflect adaptive strategy during species and local population establishment. Four experimental populations of L. longiflorum and five of L. formosanum with different locality co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…L. longiflorum populations showed annual biomass 3.3 to 13.5 times less than L. formosanum populations (Hiramatsu et al, 2002). In our experiment, FFU populations produced adequate scaly leaves during the six months after seed culture to develop sufficient stem leaves to start the reproductive phase.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…L. longiflorum populations showed annual biomass 3.3 to 13.5 times less than L. formosanum populations (Hiramatsu et al, 2002). In our experiment, FFU populations produced adequate scaly leaves during the six months after seed culture to develop sufficient stem leaves to start the reproductive phase.…”
Section: Discussionmentioning
confidence: 50%
“…It was shown that the high precocious flowering ability of L. formosanum and L. longiflorum populations in the southern Ryukyu Archipelago and Taiwan shifted the anthesis time from early to mid-summer (August to early September) to ensure biomass accumulation for flowering in the first year of these populations (Hiramatsu et al, 2002;Saruwatari, 2009). Low degrees of flowering rate and slight net production during spring to summer in the first year of northern L. longiflorum populations (Hiramatsu et al, 2002) associated with quiescence in leaf development during summer, suggested the theory that the precocious flowering ability is an adaptive strategy to grow without dormancy throughout the year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lilium species take several years to start flowering from the time of seed sowing; for example, L. auratum Lindley, L. speciosum Thunb., and L. rubellum Baker take 4-5 years (Shimizu, 1971). Lilium formosanum Wallace, native to mainland Taiwan, exceptionally reaches anthesis within 12 months from the time of seed germination without temperature control during the entire cultivation (Hiramatsu et al, 2002). The strong 'precocious flowering' ability of this species is a highly attractive trait in lily cut flower production for obtaining flowers in a short cultivation period and for rapid rotation of the breeding cycle.…”
Section: Introductionmentioning
confidence: 99%